The Relationship Between Food Consumption and Hypertension in the Elderly in the Working Area of the Sarimatondang Health Center, Simalungun Regency - Nur Mazdalifah; Barimbingan, Diana Lorenta (International Journal of Public Health Excellence (IJPHE), 2023)
Hypertension is currently a risk factor for morbidity and mortality for Jansia. Or Riskesdas 2013 states that the prevalence of hypertension in Indonesia ranges from 25.8 % , with more disease incidence occurring in women (28.8%) and in the elderly. In North Sumatra, the prevalence of hypertension is also high, which is around 24.7 % based on the 2013 Riskesdas data. Data from the Sarimatondang Health Center states that the prevalence of hypertension in the elderly is around 21 people (8.8 % ). The purpose of this study was to determine and analyze the relationship between food consumption and the incidence of hypertension in the elderly at the Sarimatondang Health Center in 2018. This type of research is an observational analytic with a cross-sectional study design. The population in this study were all elderly aged ≥ 60 years at the Sarimatondang Health Center, totaling 120 people, with a sample size of 55 respondents. This research was conducted at the Sarimatondang Health Center from 2018 to August. The results showed that the types of food to prevent hypertension that were often consumed by respondents were corn, fresh water fish, tempeh, tomatoes, bananas, green beans and the types of foods that triggered hypertension which were often consumed by respondents were pork, salted fish, and biscuits. The results also showed that the variables significantly related to the incidence of hypertension were fat (p=0.025), sodium (p0=039) and fiber (p=0.029), while carbohydrates (p=0.821) and protein (p=0.189). ) was not significantly associated with the incidence of hypertension. Advice that can be given to the community at the Sarimatondang Health Center in 2018, especially the elderly, is to reduce consumption of foods that are high in sodium or salt, high in fat, and also increase consumption of vegetables and fruit at affordable prices every day.